2-Prime Hyperideals of Multiplicative Hyperrings - Mahdi Anbarloei (Journal of Mathematics)
Multiplicative hyperrings are an important class of algebraic hyperstructures which generalize rings further to allow multiple output values for the multiplication operation. Let R be a commutative multiplicative hyperring. A proper hyperideal I of R is called 2-prime if x∘y⊆I for some x,y∈R, then, x2⊆I or y2⊆I. The 2-prime hyperideals are a generalization of prime hyperideals. In this paper, we aim to study 2-prime hyperideals and give some results. Moreover, we investigate δ-2-primary hyperideals which are an expansion of 2-prime hyperideals.